Perceptions on Indigenous Medicine, First Aid and Treatment of Snakebite among Sri Lankan Farmers - Herath, HMP; Banneheka, BMHSK; Marikar, FMMT (International Journal of Human and Health Sciences (IJHHS), 2024)
Since snakebite is a serious public health concern in Asia, one of the most affected countries is Sri Lanka. The incidence, species variety, clinical symptoms, and management of snakebite in Asia, with a focus on Sri Lanka, are all covered in this review paper. Many of the venomous snake species found in Asia are abundant and diverse. Snake bites are a typical occurrence, especially in rural areas where farming and encounters between humans and snakes are common. Numerous snake species, including the dangerous Russell’s viper and the spectacled cobra, are found in Sri Lanka specifically. Depending on the type of snake bitten and the amount of venom administered, different clinical symptoms might result from a snake bite. Pain, bruising, swelling, and systemic symptoms like nausea, vomiting, and paralysis are typical ones. Treatment that is given too slowly or not at all can result in fatal consequences. Antivenom delivery, wound care, and supportive measures are all essential components of managing snake bite cases effectively. However, obstacles including a lack of access to medical facilities and less availability of antivenom sometimes make it difficult to get treatment quickly, particularly in isolated places and concern about indigenous treatment as well. Public awareness campaigns, better healthcare facilities, and epidemiology research are only a few of the measures taken against snakebite in Sri Lanka. To lessen the number of snakebites in, government institutions, medical professionals, and international organizations must work together. Better antivenom medicines and improved preventive and treatment plans for snakebite in this area require more study and funding. International Journal of Human and Health Sciences Vol. 08 No. 02 Apr’24 Page: 116-125